A Novel Method for the Synthesis of Triphenylenes - S. Abou-Teim, Omar (Asian Journal of Chemistry, 2010)
A novel method is described for the synthesis of triphenylenes, which involves the coupling of 1,2-diiodobenzenes using copper bronze. Many compounds were synthesized using this method.